Komunikasi Interpersonal Dan Interaksi Sosial Terhadap Tingkat Partisipasi Krama Banjar di Desa Jagaraga Indah - Sutriani, Ida Ayu Nyoman (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2020)
This study aims to determine the effect of interpersonal communication and social interaction on the level of participation of Krama Banjar in Jagaraga Indah Village, Kediri District, West Lombok, both partially and simultaneously .This research is supported by cognitive theory, behavioristic theory, conflict theory, decision making theory, implementation theory, and evaluation theory. This study is a causal associative study with a population of banjar krama of four banjar totaling 311 krama banjar . The number of samples based on the calculation of the Roscoe formula is 104 banjar manners. The data collection method uses a questionnaire. Data analysis techniques used multiple regression analysis. The results of this study indicate that partially interpersonal communication variables have no significant effect on the level of participation in banjar manners with a t- test result of 1.046 and a significant value of 0.298 > 0.05, while the social interaction variable has a significant effect on the level of participation of the banjar krama with the results of t count of 7.797 with a significance of 0,000 < 0.05. Simultaneously interpersonal communication and social interaction significantly influence the level of participation in banjar manners with an F count of 47.479 with a significance of 0.000 < 0.05. From these results it can be concluded that interpersonal communication is not going well to increase the participation of banjar manners , while social interaction goes well which can increase the participation of banjar manners . Interpersonal communication and social interaction can simultaneously increase the participation of Krama Banjar in Jagaraga Indah Village, Kediri District, West Lombok.